Clinical and Dermoscopic Determinants of Surgical Decision-Making in Skin Cancer Screening: A Retrospective Analysis - Adrian Chwojnicki; Sebastian Makuch; Hanna Adamska; Michalina Świetlicka; Maja Hrynczyszyn; Inga Buława; Paulina Piesch; Jacek Polański; Wojciech Tański (Medicina, 2026)
Background and Objectives: Deciding which pigmented or non-pigmented skin lesions require surgical excision, as opposed to continued observation, is a common challenge in everyday dermatologic practice. Although dermoscopy is well established as a tool that improves melanoma detection accuracy compared with naked-eye examination, real-world evidence on how demographic profile, patient history, and dermoscopic impression jointly influence the surgical decision remains limited. This study examined the clinical and dermoscopic factors associated with a positive surgical decision (PSD) in a large single-centre screening cohort. Materials and Methods: This retrospective cross-sectional analysis included 643 consecutive patients (415 female (64.5%), 228 male (35.5%); mean age 51.3 ± 16.8 years) undergoing dermoscopic skin cancer screening. Data recorded included family history of melanoma (FHM), personal history of skin cancer (HSC), childhood sunburn (CS), clinically atypical lesions (CAL), suspicion of basal/squamous cell carcinoma (BCC/SCC), nevus count (NC, 0–4), and the surgical decision (PSD). Free-text dermoscopic descriptions were grouped into seven diagnostic categories. Group comparisons used the Mann–Whitney U, χ2, and Fisher’s exact tests; predictors of PSD were characterised using multivariable logistic regression (with Hosmer–Lemeshow and Nagelkerke R2 statistics), multiple correspondence analysis (MCA), Gower-distance k-medoids clustering, and receiver operating characteristic (ROC) analysis, including the area under the curve (AUC). Missing NC data (13.2%) were assessed using Little's test for data missing completely at random (MCAR test). Results: A positive surgical decision was recorded in 133/643 patients (20.7%) and was significantly more common in men than women (25.9% vs. 17.9%; p = 0.017; corresponding to an odds ratio (OR) of 1.61). In multivariable analysis, suspicion of BCC/SCC (OR = 24.7, 95% confidence interval (CI): 9.26–66.0) and clinically atypical lesions (OR = 5.53, 95% CI 3.50–8.74) were the strongest independent predictors of PSD (Nagelkerke R2 = 0.31; Hosmer–Lemeshow p = 0.977), far outweighing family or personal history. A significant interaction between childhood sunburn and nevus count (OR = 1.39, 95% CI 1.16–1.66; p < 0.001) predicted clinical atypia. Missing NC data were consistent with a completely random pattern (Little’s χ2 = 2.80, df = 2, p = 0.247). Dermoscopic impression showed strong discriminative value for PSD: “no concern” had the highest negative predictive value (NPV = 0.927; AUC = 0.762), while “atypical lesion” combined high specificity (0.916) and positive predictive value (0.632; AUC = 0.736). On average, 4.8 patients were examined for every surgical referral generated (a screening-to-referral ratio, not a number needed to screen for a histologically confirmed cancer). Conclusions: Surgical decision-making in this cohort was driven almost exclusively by the dermoscopic impression—suspected BCC/SCC and clinical atypia—rather than by family or personal oncological history, while male sex was independently associated with a higher surgical rate. These findings support dermoscopy-led triage protocols and highlight the potential value of standardised risk stratification to optimise referral pathways in routine skin cancer screening.